Every nonlinear element from Chua's table can generate pinched hysteresis loops: generalised homothety theorem. Issue 21 (1st October 2016) - Biolek, D.; Biolek, Z.; Biolkova, V.
Abstract : The pinched hysteresis loops drawn in the voltage–current, voltage–charge, and flux–current characteristics belong to well‐known fingerprints of the memory elements known as the memristor, memcapacitor, and meminductor. It is shown that generating such loops is in fact a natural attribute of all nonlinear elements from Chua's table, and that the hysteresis need not necessarily be a manifestation of the internal memory of the element. A generalised homothety theorem is introduced, which describes the regularities of such a hysteresis and its frequency dependence.